The Relics of the True Cross: An Interdisciplinary approach. - Kazan Georges; Higham Thomas (Taylor & Francis, 2022)
The Wood of the Cross upon which Jesus Christ was crucified is the greatest Christian relic of all. In materialising the memory of Christ’s suffering, it paved the way for the public circulation and veneration of other relics within Christianity, such as the bones of martyrs. Such relics were highly valuable and easy to counterfeit. At the Reformation, the sheer quantity of Wood of the Cross in circulation made it a target for Protestant theologians seeking to impugn the authority of the Roman Catholic Church. In response, Catholic scholars began to undertake the first scientific studies of relics. The history of the Wood of the Cross therefore offers new insights nor only into the development of the Christian world, but also into its scientific methods and concepts of materiality. Today, in the twenty-first century, analyses have become available that permit us to obtain robust data from materials such as wood and bone. Set within the context of the written sources, this can provide new historical information concerning the origins, circulation and veneration of Christian relics. The present article sets out current research aims, provides a general overview of the historical and material evidence and proposes methods suitable for an integrated study of the Wood of the Cross. These will be developed further as the authors’ research progresses.
Relics, Shrines and Pilgrimages Sanctity in Europe from Late Antiquity